Pelatihan Penerapan Keamanan Akses Jaringan Komputer di SMK Negeri 1 Cikarang Selatan - Susilo, Arif; Eko Putra, Fibi; Ermanto, Ermanto; Indra Prasetya, Dwi; Suryadi, Suryadi (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
The rapid development of information technology requires the improvement of human resource competencies, particularly in the field of computer network security. SMK Negeri 1 Cikarang Selatan, as a vocational high school focusing on information technology, has significant potential to produce work-ready graduates; however, it still faces limitations in students’ knowledge and skills related to network access security implementation. The main problems identified include low network security literacy, limited technical skills in configuring security systems, and a lack of digital ethics awareness in network usage. This community service program aims to enhance students’ knowledge, practical skills, and awareness of the importance of computer network access security through structured and application-oriented training. The implementation method consists of preparation, socialization, theoretical and practical training, case study simulations, evaluation, and follow-up for program sustainability. Training materials cover password management, firewall configuration, VPN usage, two-factor authentication, and role-based access control. The expected outcomes of this program are improved student competence in applying network security practices, optimized utilization of the school’s computer laboratory, and the establishment of a digital security awareness culture within the school environment. This program also contributes to enhancing the competitiveness of vocational school graduates in meeting industry demands and technological advancements. Keywords: network security, network access, training, vocational school, information technology.